Planting the Foundations of a Post-2020 Land Sector Reporting and Accounting Framework - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2014)
Land management faces a series of daunting challenges in the 21st century. These include contributing to the global mitigation effort and adaptation needed to prevent dangerous climate change, while providing enough food for a population of 9 billion by 2050 as well as shelter and livelihoods for rural populations and various ecosystem services. The existing mitigation reporting and accounting arrangements for the land sector are complex, not applicable to all Parties, and provide limited scope for pursuing more costeffective accounting approaches that would enable developing countries to address conflicting policy objectives such as addressing climate change while increasing agricultural output. This paper has two aims. The first is to lay out possible elements of a long-term vision for the post-2020 reporting and accounting framework for emissions and removals from the land sector, building on existing experience with reporting and accounting as well as previous studies. The second is to identify possible steps that could be taken at COP 20 in 2014, COP 21 in 2015, and in 2016-2020 to put Parties on a pathway towards realising this vision